Implementasi Kebijakan Pencegahan Perkawinan pada Usia Anak oleh Dinas Pengendalian Penduduk, Keluarga Berencana, Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Buleleng - Madyni, Manik; Aripin, Sofjan; Widnyani, Ida Ayu Putu Sri (Syntax Corporation, 2025)
child marriage is one of the social problems in Buleleng Regency. The results showed that programs and activities in policy implementation have been pursued since the policy was issued in 2015, but policy implementation has not been optimal. Each implementing agent in policy implementation understands the idea of preventing child marriage and is committed to contributing to policy implementation. However, suboptimal communication and coordination hinder the optimal implementation of activities. A unique finding in this study is the existence of awig-awig or traditional village regulations that contain prohibitions on early marriage, so there are additional rules besides formal regulations. The lack of involvement of actors outside the government, especially traditional leaders and NGOs, is one of the main obstacles to policy effectiveness. In addition, budget limitations lead to a lack of sustainable activities, especially in remote areas. Therefore, a better collaborative strategy is needed as well as an increase in the role of the community to support child marriage prevention policies.